Restoring natural hair pigmentation: clinical assessment of safety and efficacy of an ayurvedic leave-on treatment - Madhavi, M. S. Lakshmi; Shukla, Ravi Kant; Gudulkar, Susmita; Mathur, Saurabh; Punyani , Supriya (International Journal of Research in Dermatology, 2025)
Background: This clinical study evaluated the safety and efficacy of an Ayurvedic leave-on treatment for premature hair greying in healthy Indian adults (male and female). It also investigated the product’s mechanism of action through in vitro analyses. Methods: Healthy male and female volunteers aged 20–42 years with early-onset hair greying and no underlying medical conditions were enrolled in the clinical study. Participants were screened based on predefined criteria, including a specific percentage of grey hair. The study included a washout period before treatment initiation, followed by a four-month application phase with regular follow-ups. An in vitro study using B16F10 melanocytes (ATCC) was also conducted to explore the Ayurvedic leave-on treatment’s mechanism of action. Results: The Ayurvedic leave-on treatment significantly increased natural black hair density and reduced grey hair count in both male and female subjects. In vitro analysis reveals that the Ayurvedic leave-on treatment enhances melanogenesis by upregulating melanin production in melanocytes. Conclusions: The present study concludes that the Ayurvedic leave-on treatment promotes melanogenesis, reduces oxidative stress, provides cytoprotective benefits, and effectively enhances dark hair density while reducing grey hair count. Clinically, 100% of users showed improved dark hair density, 97% reported reduced grey hair. No adverse effects were observed, confirming its safety and efficacy for both men and women with greying concerns.